Emulation of battery discharge behaviour using programmable power supply based on LabVIEW - N. Tanruean; Chinda Charoenphonphanich; T. Yenwichai; Manop Masomtob (IOP Conference Series Materials Science and Engineering, 2021)
Abstract This paper presents a battery simulator based on the actual electrical behaviour of the battery cells using power supply controlled by Laboratory Virtual Instrument Engineering Workbench (LabVIEW). Firstly, the behaviours of the battery are tested under experimental conditions including constant temperatures at 25C˚ and two different current loads at 0.5C and 1C. Secondly, the battery behaviours are analysed and applied in LabVIEW. The algorithms which are low pass filter, PID and others are implemented in LabVIEW to reduce standard deviations and errors. The current study found that the constant load at 0.5C and 1C, which controlled by the electronic load via LabVIEW, can emulate the battery voltage and the error relative is below 5 %. Further work is required to establish the optimization of the parameters in the battery management system (BMS) since a battery simulator uses power sources before the use of the battery management system (BMS) with a real battery.
Keywords: Advanced Battery Technologies Research; Fault Detection and Control Systems; Industrial Automation and Control Systems